Pengaruh Hallyu Wave, Brand Image dan Celebrity Endorsement Terhadap Keputusan Pembelian Produk Kosmetik Barenbliss (Bnb) di Daerah Istimewa Yogyakarta - Hernda Putri Prabandaru; Awan Santosa (Jurnal Perilaku dan Strategi Bisnis, 2025)
This study aims to examine the influence of Hallyu Wave, Brand Image, and Celebrity Endorsement on the Purchase Decision of Barenbliss (BNB) cosmetic products in the Special Region of Yogyakarta. The research employs a quantitative approach with descriptive and causal (cause-and-effect) research types. Data were collected through questionnaires used as research instruments, involving a total of 100 respondents. The population of this study comprises all Barenbliss (BNB) consumers in the Special Region of Yogyakarta who have made purchases at least once in the past four months, with purposive sampling applied as the sampling technique. The results indicate that Hallyu Wave has no significant effect on Purchase Decisions, while Brand Image has a positive and significant effect on Purchase Decisions. In contrast, Celebrity Endorsement also shows no significant effect on Purchase Decisions. However, when considered simultaneously, Hallyu Wave, Brand Image, and Celebrity Endorsement collectively have a significant effect on Purchase Decisions. These findings suggest that although the Hallyu Wave and Celebrity Endorsement variables do not have partial effects, their presence within the model still contributes when combined with Brand Image. The findings of this study are expected to contribute to the development of academic knowledge and marketing strategies for business practitioners in the beauty industry (cosmetics and personal care), enabling a deeper understanding of consumer preferences and perceptions in making purchase decisions.